(untitled) (Pulse, 2015)
Objective: To know effect of hematoma and perihematomal edema volume on Glasgow Coma Scale (GCS) at the time of admission in patients with spontaneous lobar and basal ganglia hemorrhage. Methods: this cross sectional study was conducted in Neurosurgery department, BSMMU to observe effect of hematoma and perihematomal edema volume on GCS at the time of admission in patients with spontaneous lobar and basal ganglia hemorrhage. The duration of study period was from November 2005 to April 2007. Results: a total 48 patients were included in the study and the variables that were analyzed included site of hematoma, volume of hematoma, perihematomal edema and the initial GCS score. Associations between the hematoma and perihematomal edema, site of hemorrhage and perihematomal edema, hematoma volume and GCS at the time of admission, perihematomal edema volume and GCS at the time of admission were evaluated. Level of consciousness (GCS) at the time of admission is the key factor in predicting outcome and neurological deterioration. In our study we found significant association between- hematoma and perihematomal edema volume, hematoma volume and GCS at the time of admission, perihematomal edema volume and GCS at the time of admission. But there was no significant association found between hemorrhage site and perihematomal edema. Conclusion: more the volume of hematoma more was the volume of perihematomal edema. More the volume of hematoma less was the GCS. More the volume of perihematomal edema less was the GCS. But we found no significant association between site of hemorrhage and perihematomal edema volume. GCS is an established predictor of outcome in patients with SICH (spontaneous intracerebral hemorrhage). Accurate prediction of the outcome in ICH patients is important for several reasons: a reliable prognosis must be given to patient and relatives as soon as possible, realistic rehabilitation goals should be set and resources should be allocated in the most efficient way. Pulse Vol.7 January-December 2014 p.22-28